Danger-Sensing/Patten Recognition Receptors and Neuroinflammation in Alzheimer’s Disease - Anna Chiarini; Ubaldo Armato; Peng Hu; Ilaria Dal Prà (2020)
Fibrillar aggregates and soluble oligomers of both Amyloid-β peptides (Aβs) and hyperphosphorylated Tau proteins (p-Tau-es), as well as a chronic neuroinflammation are the main drivers causing progressive neuronal losses and dementia in Alzheimer's disease (AD). However, the underlying pathogenetic mechanisms are still much disputed. Several endogenous neurotoxic ligands, including Aβs, and/or p-Tau-es activate innate immunity-related danger-sensing/pattern recognition receptors (PPRs) thereby advancing AD's neuroinflammation and progression. The major PRR families involved include scavenger, Toll-like, NOD-like, AIM2-like, RIG-like, and CLEC-2 receptors, plus the calcium-sensing receptor (CaSR). This quite intricate picture stresses the need to identify the pathogenetically topmost Aβ-activated PRR, whose signaling would trigger AD's three main drivers and their intra-brain spread. In theory, the candidate might belong to any PRR family. However, results of preclinical studies using in vitro nontumorigenic human cortical neurons and astrocytes and in vivo AD-model animals have started converging on the CaSR as the pathogenetically upmost PRR candidate. In fact, the CaSR binds both Ca2+ and Aβs and promotes the spread of both Ca2+ dyshomeostasis and AD's three main drivers, causing a progressive neurons' death. Since CaSR's negative allosteric modulators block all these effects, CaSR's candidacy for topmost pathogenetic PRR has assumed a growing therapeutic potential worth clinical testing.